Entre as rotas da formação: o professor de educação especial na perspectiva da educação inclusiva - Bernardes, Daniela (2019)
This dissertation shows an investigation developed at the Master Course from the Post-Graduation Program in Education, in the research area of Special Education at the Federal University of Santa Maria (UFSM). This research also articulates with studies realized by the Group of Studies and Research in Special Education and Inclusion (GEPE). In this study, it was aimed at problematizing, from final course papers (TCCs) of academics from the Teaching Course of Special Education, the ways in which the special education teacher performance to act in basic education in the perspective of Inclusive Education appears or is systematized. Methodologically, the research was produced from the analogy of “paths”, considering the choices of a route for a walk, which started to be built from the readings and in the work of systematizing what is written in the TCCs, understanding that it is from the research materials that it is possible to see the research steps. The understanding of the TCCs was problematized by the search of wording that could allow answering the research question: How does the initial formation of special Education teachers have been preparing teachers to act in Basic Education in the perspective of Inclusive Education? Such project aimed at discussing the ways the systematized performances act in the initial formation of those teachers in the basic education from the perspective of inclusive education. In order to achieve this objective, the following goals were established: to identify the diversity of discourses which produce the inclusion as an adjective for Basic Education; to track, in academics’ writings, from the past 6 years (2012-2017), the discourses about the ways to constitute teachers of special education in basic education with the inclusive perspective; to recognize the different manners of spreading the ways of conceptualizing and saying the performance of Special education teachers in Basic Education with the inclusive perspective, which take part in the initial formation of the Teaching Course of Special Education at UFSM. These goals helped thinking the formative moves, tracking and recognizing the discourses of undergraduates from the Teaching Course of Special Education from UFSM about inclusion. These students say and produce some practices that constitute the field production, sustaining the formation of inclusive teachers, the one from the Special Education.